ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEANDALAN DAN KETEPATAN LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH PADA PEMERINTAH KABUPATEN MINAHASA TENGGARA - Kosegeran, Anando Iphan; Kalangi, Lintje; Wokas, Heince (Universitas Sam Ratulangi, 2016)
This research is motivated by the fact that the financial statements of local government in Fiscal Year 2008 through Fiscal Year 2012, getting Disclaimer opinion of the Audit Board of the Republic of Indonesia Representatives of the Province of North Sulawesi. Therefore, with stronger demand and transparency of public institutions, both the center and in the regions, the researchers are interested in examining the